Protection of Non-Participating Creditors in PKPU Homologation: Reconstruction of the Creditorum Parity Principle and the Fairness Test of Results - Ferry Febri Mewengkang; Adnan Hamid; Sonyendah Retnaningsih; Zaitun Abdullah (Lembaga Teewan Journal Solutions, 2026)
This study examines the legal protection of non-participating creditors in the homologation of Suspension of Debt Payment Obligations (PKPU) under Indonesian bankruptcy law. Although homologation binds all creditors, including those who do not participate in the proceedings, Law Number 37 of 2004 primarily emphasizes procedural legitimacy through voting and quorum requirements without explicitly assessing the fairness of outcomes. This research employs a normative juridical method using statutory and conceptual approaches supported by grammatical, systematic, and teleological interpretation of relevant legal provisions and doctrines. The analysis reveals that the current PKPU framework allows non-participating concurrent creditors to receive substantially lower recoveries than they would reasonably obtain in bankruptcy, thereby conflicting with the principles of paritas creditorum and pari passu pro rata parte embodied in Articles 1131 and 1132 of the Indonesian Civil Code. Furthermore, the substantive review authority granted to judges under Article 285 has not been fully utilized to protect vulnerable creditors. This study proposes strengthening the application of the paritas creditorum principle through an Indonesian version of the best interests of creditors test as a fairness benchmark during homologation, ensuring that restructuring promotes legal certainty while safeguarding equal treatment and distributive justice for all concurrent creditors.